(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2021)
On July 14, 2021, the Constitutional Court declared unconstitutional some of the provisions set forth in Royal Decree 463/2020, of March 14, declaring a state of alarm for the management of the health crisis caused by COVID-19. The judgment based its argument on the fact that these restrictions constituted a suspension of the freedom of movement and not a mere limitation. This made them incompatible with art. 55 of the Spanish Constitution, which establishes that the suspension of certain rights can only occur under states of emergency and siege. The ruling has given rise to a doctrinal debate on the interpretation of emergency law and the role of the institutions.